Ski jumping take-off in a wind tunnel with skis - Virmavirta, M.; Komi, P. V. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
on the take-off action. However, wind tunnel experiments have recently been utilized to study take-off aerodynamics in ski jumping (Virmavirta et al. 2001). In these measurements the decreased take-off time in wind conditions was regarded as resulting from a reduced load under the influence of aerodynamic lift. The purpose of the present study was to examine whether it is possible to repeat the procedure of Virmavirta et al. (2001) with skis and characterize the effects of skis on force-time profile of the ski jumping take-off. Preliminary results of one jumper are presented in this paper. Methods Ground reaction forces were recorded under the fore and rear foot area separately with the special force plate in-stalled under the wind tunnel floor during simulated ski jumping take-offs with skis in non-wind and wind (14 - 29 m/s) conditions. The airflow at the boundary surface of the tunnel floor was controlled by using perforated fence (5 cm) for ensuring the proper behaviour of skis at the release instant. Results Figure 1 shows that the jumper was able to perform very natural take-off action with skis in wind tunnel. According to the subjective feeling of the jumpers, the simulated ski jumping take-off with skis was even easier to perform and more natural as compared to the earlier trials without skis. Decreased take-off time was found in all take-offs per-formed in wind conditions and it was still evident with skis as well (8 %, p< 0.05 as compared to non-wind condition with skis). Discussion/Conclusion It seems that skis did not influence much the force levels produced (average and max forces) during the take-off but they still changed the force distribution under the feet (fig. 2). Contribution of the forces produced under the rear part of the feet was emphasized probably because of the dorsiflexion needed for lifting the skis to the proper flight posi-tion. Ski bindings also allow the slight backward leaning at the initial phase of the take-off. It can be concluded that this experiment certainly brought the research of simulated ski jumping take-off again one step closer to the real take-off situation.